Knowledge, attitudes and practices of Materiovigilance among physicians in a rural tertiary care teaching hospital in Puducherry- a cross sectional study - M, Sakthibalan; Adhimoolam, Mangaiarkkarasi; C, Indumathi (Creative Pharma Assent, 2024)
Background: In India, medical devices are considered as drugs. A medical device may lead to problems either due to a defect during manufacture or transport, improper handling by health care professionals or patients, or failure to comply with recommendations. Aim & Objective: To evaluate the knowledge, attitude, and practice of Materiovigilance among health professionals at the Tertiary Care Hospital. Methods: This was a Cross-Sectional Questionnaire Based study. The questionnaires were circulated among 100 medical professionals. The structured survey tool comprised of two parts. The first part contains demographic data, and the second part consists of 15 questions, with 5 each pertaining to the awareness, attitude, and practice domains. All the data were entered into a Microsoft Excel sheet and analyzed using GraphPad Instat software version 5.0. Results: Medical professionals with above-average knowledge scores were 57 %, and the practice percentage of Materiovigilance was 60%, but there is a positive attitude (72%) towards Materiovigilance. A significant difference was noted Between the knowledge scores of professors and residents (p-value - 0.0491). There was no significant difference in knowledge scores between medical, surgical, and pre/para specialties. However, there was a positive correlation between the knowledge and attitude scores of the medical professionals. Conclusion: We conclude that the Knowledge aspect and also the practice of Materiovigilance among Physicians in our tertiary care hospital is lacking. However, their positive attitude to reporting adverse events is reassuring.